2017
DOI: 10.1186/s40543-017-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organic acids of tricarboxylic acid cycle in plants using GC-MS, and system modeling

Abstract: Background: Leaves of 15 plant species were collected from the catchment areas of the river Beas, Punjab, India, and analyzed for organic acids of tricarboxylic acid cycle, viz., citric acid (CA), succinic acid (SA), fumaric acid (FmA), and malic acid (MA). Methods: Gas chromatography-mass spectrometry (GC-MS) was used to determine the content of organic acids in the leaves of plant species. Two microliters of plant sample was injected into the GC-MS, and the concentration of organic acids was quantified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…In a TCA cycle, citric acid and malic acid are generally the most accumulated organic acids in plants [52]; at the same time, Crocus leaves have an increased content of malic acid during acclimatization to the low temperature [53,54] of Ukraine in the postharvest period. In addition, the path analysis of the effects of different acids on malic acid content revealed that citric acid has a maximum direct effect on malic acid [55]. Furthermore, 3,3-dimethylacrylic acid, 4-hydroxybutanoic acid, and lactic acid were found in amounts of 187 µg/g, 162 µg/g, and 98 µg/g, respectively.…”
Section: Gc-ms Analysis Of Amino Acids and Short-chained And Long-chain Carboxylic Acidsmentioning
confidence: 97%
“…In a TCA cycle, citric acid and malic acid are generally the most accumulated organic acids in plants [52]; at the same time, Crocus leaves have an increased content of malic acid during acclimatization to the low temperature [53,54] of Ukraine in the postharvest period. In addition, the path analysis of the effects of different acids on malic acid content revealed that citric acid has a maximum direct effect on malic acid [55]. Furthermore, 3,3-dimethylacrylic acid, 4-hydroxybutanoic acid, and lactic acid were found in amounts of 187 µg/g, 162 µg/g, and 98 µg/g, respectively.…”
Section: Gc-ms Analysis Of Amino Acids and Short-chained And Long-chain Carboxylic Acidsmentioning
confidence: 97%
“…The organic acids in edible flowers were estimated by gas chromatography, after methylation, following the methods reported by Sharma et al (2016) and Kumar, Sharma, Bhardwaj, and Thukral (2017), using a column HP-5MS (30 m × 0.25 mm ID × 0.25 μm thickness ultra-inert capillary column, Agilent Technologies) instead of the DB-5 ms column mentioned by the authors. Individual standards of citric, levulinic, fumaric, succinic, malic, salicylic, hydroxycinnamic, malonic, oxalic, tartaric, and benzoic acids, were obtained from Sigma-Aldrich (St. Louis, USA), and were derivatized under sample conditions.…”
Section: Organic Acidsmentioning
confidence: 99%
“…Individual standards of citric, levulinic, fumaric, succinic, malic, salicylic, hydroxycinnamic, malonic, oxalic, tartaric, and benzoic acids, were obtained from Sigma-Aldrich (St. Louis, USA), and were derivatized under sample conditions. Quantification was based on individual calibration curves, using specific m/z for each compound, as detailed in Kumar et al (2017).…”
Section: Organic Acidsmentioning
confidence: 99%
“…The organic acids in the edible flowers were determined by gas chromatography, after methylation, following the procedure described by Sharma et al (2016) and Kumar, Sharma, Bhardwaj, and Thukral (2017), with minor modifications. The analytical column used was a HP-5MS (30 m × 0.25 mm i.d.…”
Section: Organic Acidsmentioning
confidence: 99%
“…Individual standards of citric, levulinic, fumaric, succinic, malic, salicylic, hydroxycinnamic, malonic, oxalic, tartaric and benzoic acids -all supplied by Sigma Aldrich (Germany) -were derivatized under sample conditions. Quantification was based on individual calibration curves, using specific m/z for each compound, as detailed in Kumar et al (2017).…”
Section: Organic Acidsmentioning
confidence: 99%